A Study of the Solid Waste Chain in Benin Metropolis, Nigeria - Dennis Iyeke Igbinomwanhia; Ejovo Nena Ohwovoriole (Journal of Applied Sciences and Environmental Management)
Benin metropolis like other fast urbanizing towns and cities in Nigeria is faces with a solid waste management problem. Solid waste is seen in huge heaps on any piece of unused land, around buildings, in the open market places and in drainage and water ways. The work reported in this paper involves a study of the path traced by solid waste in the process of management in Benin metropolis. Structured questionnaires were applied to collect primary information such as size of method of waste disposal, Educational level, monthly income etc. from households. Solid waste dump sites – legal and illegal were visited. Water drainages were also observed during the study. The results obtained indicated that poor education, poor income of residence, none existence of solid waste data and insufficient funding for solid waste management are the major causes of solid waste management problems in Benin metropolis. Some feasible suggestion for improved management of solid waste based on the prevailing economic and educational state of the residents in the metropolis has been presented. @JASEM